MINAT KELOMPOK WANITA TANI (KWT) PADA PERTANIAN PERKOTAAN MELALUI BUDIDAYA SAYURAN SECARA VERTIKULTUR DI KECAMATAN SERPONG KOTA TANGERANG SELATAN - Nadila Aningtyaz; Harniati Harniati; Dedy Kusnadi (Sekolah Tinggi Pariwisata Mataram, 2020)
Verticulture is the simplest cultivation system that can be conducted in urban areas by utilizing limited land due to dense population settlements. This cultivation system is one of the solutions for agricultural development in urban areas where women farmer groups (WFG) in Serpong Sub-district experience limited land to conduct farming activities. This assessment aims to describe the interests, analyze the factors that affect interest, and formulate strategies to increase the interest of women farmer groups (WFG) in urban agriculture through verticultural cultivation of vegetables. The assessment has been carried out in Serpong Sub-district, South Tangerang City from April to June 2020. The assessment sample was determined by the saturation sampling technique of 31 members who are members of WFG Az-Zahra and WFG Mawar. The assessment variables consist of internal factors, external factors, and interests. Analysis of the data used in this assessment is descriptive statistical analysis, multiple linear regression analysis, and develop the two results of the analysis which are translated into strategies to increase interest. The results of the assessment showed that the interest in WFG in urban agriculture through verticultural vegetable cultivation was in the medium category with a percentage of 67.7 percent. Factors influencing WFG interest are the function of farmer groups, family environment, community environment, and extension activities. The strategy to increase the interest of WFG can be conducted by increasing the participation of all WFG members in group farm activities, encouraging and directing through counseling activities, and involving WFG members by holding demonstrations on how to cultivate vegetables vertically.